Allo‐reactive T cells for the treatment of hematological malignancies1. Issue 10 (24th October 2015) - Falkenburg, J.H.F.; Jedema, I.
Abstract : Several mechanisms can be responsible for control of hematological tumors by allo‐reactive T cells. Following allogeneic stem cell transplantation (alloSCT) donor T cells recognizing genetic disparities presented on recipient cells and not on donor cells are main effectors of tumor control, but also of the detrimental graft versus host disease (GVHD). Since after transplantation normal hematopoiesis is of donor origin, any T cell response directed against polymorphic antigens expressed on hematopoietic recipient cells but not on donor cells will result in an anti‐tumor response not affecting normal hematopoiesis. After fully HLA‐matched alloSCT, T cells recognizing polymorphic peptides derived from proteins encoded by genes selectively expressed in hematopoietic lineages may result in anti‐tumor responses without GVHD. Due to the high susceptibility of hematopoietic cells for T cell recognition, a low amplitude of the overall T cell response may also be in favor of the anti‐tumor reactivity in hematological malignancies. A mismatch between donor and patient for specific HLA‐alleles can also be exploited to induce a selective T cell response against patient (malignant) hematopoietic cells. If restricting HLA class II molecules are selectively expressed on hematopoietic cells under non‐inflammatory circumstances, allo HLA class‐II responses may control the tumor with limited risk of GVHD. Alternatively, T cells recognizing hematopoiesis‐restricted antigens presented in the context of mismatched HLA alleles may be used to treat patients with hematological cancers. This review discusses various ways to manipulate the allo‐immune response aiming to exploit the powerful ability of allo‐reactive T‐cells to control the malignancies without causing severe damage to non‐hematopoietic tissues. Highlights: After allogeneic stem cell transplantation normal hematopoiesis is of donor origin. Donor T cells can mediate effective anti‐tumor effects. Donor T cells can cause graft versus host disease. Adoptive transfer of selected T cell populations can increase the specificity.